The Impact of an Escape Room Simulation to Improve Nursing Teamwork, Leadership and Communication Skills: A Pilot Project. (February 2021) - Valdes, Beatriz; Mckay, Mary; Sanko, Jill S.
Background: Commercialescape room simulation -based educational experiences were piloted on a cohort of ten RN-BSN students to determine the effect on mastery ofcommunication, leadership, andteamwork skills. Methods: Pre-test/post-test research design and qualitative questions were used to measure the impact of anescape room simulation activity onteamwork, communication, and leadership skills. The Team Strategies and Tools to Enhance Performance and Patient Safety ® Teamwork Attitudes Questionnaire, and self reported levels of confidence and competence questionnaire were administered pre/postescape room simulation to measurecommunication, team structure and leadership skills. The University of Miami-Crisis Resource Management tool was utilized to measure observedteamwork . Additionally, four open-ended qualitative self-reflective questions were asked following theescape room . Results: Data from the analysis of the pre and post observations ofsimulation encounters found statistically significant time dependent differences noting improvements in observedteamwork and leadership, p <.001, pre-mean 18.5, post-mean 35.0. Qualitative data revealed the participants found theescape room simulation to be an engaging teaching method to masterteamwork and leadership skills. Conclusion: This pilot study sets the foundation for future use and exploration ofescape room experiences to teachteamwork, communication, leadership and situational awareness. Following theescape room simulation, observed improvements inteamwork and leadership were found. Participants found theescape room activity to be an engaging experiential teaching method to promote attainment of critical skills needed to work as an effective member of a team. Study findings suggest that the use of an escape room can impart experiential learning with critical skills needed to work as an effective member of a team. As a result of this pilot study, nursing faculty developed anescape room simulation experience that was initiated the following semester.